Vulnerable young people and alcohol use: a qualitative exploration. (March 2014) - Clement, Clare; Thirlaway, Kathryn; Smith, Alyson; Williams, Jackie
<x xml:space="preserve">Abstract</x> Background: Evidence suggests vulnerable young people are at a greater risk of alcohol engagement and have higher levels of substance misuse. However, research exploring alcohol use within populations of vulnerable young people is limited. Aims: The aim of the study was to explore young people's attitudes to alcohol, seeking to gain insights into drinking practices within a group of educationally marginalised, and therefore vulnerable young people and their support staff. Methods: The views on alcohol use of 13 young people were explored through focus groups whilst the views of seven support staff were explored using semi-structured interviews. Findings: From an analysis based on grounded theory, a central theme of difficult lives appeared to mediate alcohol use in young people who are educationally marginalised. Young people appeared disengaged from parental/guardian support and placed an importance on social networks in facilitating social and peer support with the aim of gaining protection and a sense of escape. Conclusion: Educationally marginalised young people appear predisposed to an increased risk of engagement with alcohol. In their need for protection and support from daily hardships and isolation, they place greater importance of social membership, which in turn can increase the likelihood of engagement with alcohol.